Performing the (Dis)continuity of the Self in Samuel Beckett’s That Time and Edward Albee’s Three Tall Women - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Since his memorable debut with The Zoo Story at the Berlin Festival in 1959, Edward Albee has been classified as the absurdist playwright of America, his dramatic style being compared to that of Beckett by many scholars. To refer to just one device, that of the shaggy dog story at the heart of the first Albee play which encapsulates the crisis of communication portrayed by the whole, is profoundly reminiscent of the middle of Waiting for Godot where Vladimir’s song about a dog returns to its beginning like Beckett’s work itself does. Hardly a wonder, then, that in 1960, when The Zoo Story found its way home to the United States, the Greenwich Village Theater ventured to stage it as part of a double bill together with Krapp’s Last Tape. Regarding the later Beckett and Albee, the manifold links between the two are discussed by Christopher Bigsby, with special attention to the shift in their works in the direction of experimenting with the modes of presenting consciousness. In the scholar’s opinion, “Albee has been increasingly drawn to Beckett’s minimalism. His, too, are characters for whom habit has become a substitute for being. The past presses on his characters not as in a Miller play, where it is evidence of a betrayal..., but as the source of an irony which must be neutralized”, (135).